2013
DOI: 10.5999/aps.2013.40.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction of Proximal Interphalangeal Fracture-Dislocation through a Midlateral Incision Using Absorbable Suture Materials

Abstract: BackgroundFracture-dislocation of the proximal interphalangeal (PIP) joint is a relatively common injury. Various treatments for fracture-dislocation of the PIP joint have been reported. In the present study, we performed open reduction through a midlateral incision using absorbable sutures to reduce the small bone fragments and performed volar plate repair.MethodsWe treated nine patients with fracture-dislocation of the PIP joint with small fractured bone fragments too small for pinning or screw fixation. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Both dorsal, 24 volar, 25 and lateral 26 approaches have been described, using screws between 1.1-2.0 mm in size. Although an early report of two cases by Green et al reported PIPJ arcs of motion of 85° and 105°, 24 other studies have not been as favorable.…”
Section: Dorsal Fracture-dislocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both dorsal, 24 volar, 25 and lateral 26 approaches have been described, using screws between 1.1-2.0 mm in size. Although an early report of two cases by Green et al reported PIPJ arcs of motion of 85° and 105°, 24 other studies have not been as favorable.…”
Section: Dorsal Fracture-dislocationmentioning
confidence: 99%
“…25 Jay Jun Lee et al reported on the use of the lateral approach to fix small fracture fragments with absorbable suture, but on review of this study, it appears most were stable reductions, and might have done just as well without surgery. 26 …”
Section: Dorsal Fracture-dislocationmentioning
confidence: 99%
“…When fracture-dislocations to the proximal interphalangeal joint (PIPJ) 1,2 are damaged and overstretched and axial load is experienced, this causes loss of hand function and subsequent disability. PIPJ fracture-dislocation often causes many complications, such as ankylosis, joint instability, post-traumatic arthritis, and flexion contracture.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] Three studies evaluated volar plate arthroplasty: one suture-button, 56 one suture anchor, 57 and one suture repair directly to periosteum. 58 All 37 studies were LOE 4. The MINORS allow assessment of the quality of evidence in comparative and noncomparative nonrandomized trials with 0 being the lowest score and 16 being ideal for noncomparative and 24 for comparative studies.…”
Section: Demographic Data and Study Characteristicsmentioning
confidence: 99%